Perbedaan Penambahan Quadriceps Exercise Pada Terapi Micro Wave Diathermy Dan Ultrasound Terhadap Nyeri Lutut Osteoarthritis - Widi Anggraini, Noor; , Totok Budi Santoso , S.Fis , MPH; , Dwi Rosella Komala Sari S.Fis, M.Fis (2015)
Background: Pain is a common clinical symptom in patients with OA of the knee joint, especially during activity or loading. Further due to OA of the knee joint is the decrease of functional activity, especially the difficulty of rising to sit, walk, up and down stairs and others. The condition is caused by changes in the structure of the knee joint itself, ranging from narrowing between joints resulting in the joints become unstable and formation of osteophytes. Objective:This study aimed to determine the difference of therapy MWD, US and QE forpain reductionof knee OA, knowing the effect of therapeutic US andMWD forpain reductionof knee OA, and todetermine differences ineffect between therapy MWD, US andQE by the US and MWD against Oaknee pain relief. Methods:This research is a quasi experimental study. Design research is that two groups pre and post test design. In this study the author uses primary data is by taking the data before and after the intervention. The subjects of the research were used in this study were 30 subjects using consecutive sampling technique that all the samples there and met the study criteria included in the study up to the amount that need met. Test the effect on each group is used to determine the results before and after therapy. Test two groups of pairs of pre and post, then the analysis of the data used is Wilcoxon test and Mann Whitney. Results: Based on the Mann Whitney test group I to group II is the result post therapy p = 0.030 (p <0.05) means that there are significant quadriceps Exercise to decrease knee pain in patients with osteoarthritis. Conclusion: there is a positive effect of the addition of quadriceps Exercise therapy Diathemy Micro Wave and Ultrasound in reducing the degree of pain in patients with osteoarthritis. Keywords: Quadriceps Exercise, MWD & Ultrasound Therapy, Pain Knee osteoarthrosis